Submaximal heart rate and VO2max during acclimatization to living in hypoxia and training in normoxia - Rusko, H. K.; Kalliokoski, K.; Paavolainen, L.; Puranen, A.; Tikkanen, H. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
"Living high, training low" has been shown to improve sea-level performance of endurance athletes due to altitude acclimatization and maintenance of sea-level training velocities. During acclimatization plasma volume may decrease and sympathetic activation may increase influencing heart rate. Submaximal heart rate (HRsubmax) has been used to control the adaptation to training both at sea level and at altitude. In the present study, HRsubmax was studied during acclimatization to "living high, training low" in 12 experimental (HiLo) and 10 control (LoLo) endurance athletes (17 men and 5 women, age 24±4 yrs, height 176±7 cm, body mass 70±9 kg). HiLo lived 12-16 h daily for 25 days in normobaric hypoxia (O2 15.3% ~ 2500m) and trained in normoxia at sea level (100m). HRsubmax was measured during 4 * 4-min incremental cycling, in normoxia before (PRE), on days 4 (NOR4), 14 (NOR14), and 25 (NOR25) during and one week after acclimatization (POST), and in hypoxia (O2 15.3%) on days 2 (HYP2), 11 (HYP11) and 21 (HYP21) during acclimatization. Maximum oxygen uptake (VO2max) was measured at PRE and POST. LoLo lived and trained at sea level and participated in the same normoxic measurements as HiLo. Differences were not observed in the training of the two groups (10-11 h/wk). ANOVA indicated significant group by time interaction in both mHRsubmax (mean HR of the four work loads) and VO2max. During the acclimatization, in normoxia, mHRsubmax of HiLo decreased from PRE (140±10 bpm) to NOR4 (138±10 bpm, ns), NOR14 (136±7 bpm, ns), NOR25 (134±10 bpm, p<0.01) and to POST (132±8 bpm, p<0.001). In hypoxia, mHRsubmax of HiLo increased from PRE to HYP2 (147±5 bpm, p<0.001) from which it decreased to HYP11 (143±7 bpm, p<0.05) and HYP21 (140±6 bpm, p<0.001). VO2max of HiLo increased from PRE (274±37 ml/min/kg2/3) to POST (282±38 ml/min/kg2/3, p<0.01). No significant changes were found in mHRsubmax or VO2max of LoLo. At POST, mHRsubmax of HiLo was lower (p<0.05) than that of LoLo. These data suggest that submaximal heart rate in hypoxia and normoxia can be used to detect the acclimatization and training effects during "living high, training low". The results further suggest that "living high, training low" decreases submaximal heart rate and increases maximum oxygen uptake more than similar training at sea-level.